MULTI-KEYWORD SEARCH FOR DIVERSE DATA OWNERS USING ENCRYPTED CLOUD DATA - C. Nalini, Shwetambari Kharabe, G.L.Vara prasad (International Journal of Modern Agriculture, 2020)
To provide the security for information cloud computing is useful. The data owner has a facility to upload various files using this system. These files will be stored in various trashes as well as in replica also for maintaining the security.Secure ventures over encrypted cloud information have motivated a few research works under the single owner model for protection concerns.We developed this system for numerous owner’s model with different functionality. In this system, propose plans to tree based ranked multi-keyword search scheme for numerous data owners (TBMSM). By using the different keys to encrypt keywords and trapdoors helps to develop novel search protocol based on bilinear pairing efficiently. Data owner can rank the different Multikeyword search over user; user can search over encrypted data using hash value md5 or SHA 256 algorithm. Usercan also fuzzy keyword algorithm search technique also used moreover; User can download file at particular place only as well as at particular timesonly.